High-resolution strong-luminescence anti-counterfeiting material as well as preparation method and application thereof

By developing β-NaYF4:Yb/Er/Gd nanomaterials and inkjet printing technology, the complex problems of luminescence intensity and pattern preparation of fluorescent anti-counterfeiting materials are solved, and the preparation and pattern design of high-resolution strong luminescence anti-counterfeiting materials are realized, and the general purpose is achieved. and efficient production capacity.

CN119193160APending Publication Date: 2024-12-27INST OF SENSOR TECH GANSU ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411324335.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing fluorescent anti-counterfeiting materials have shortcomings in terms of luminescence intensity and complex pattern preparation steps, especially the upconversion nanomaterials lack the luminescence intensity under near-infrared excitation, and the printing platform is complex to achieve high resolution and high concealment anti-counterfeiting patterns. production.

Method used

Develop a β-NaYF4:Yb/Er/Gd nanomaterial. Through specific molar ratios and preparation processes, hexagonal nanoparticles are prepared, with uniform size and excellent morphology, and can emit green that is invisible to the naked eye under excitation of 980nm laser. Light, combined with inkjet printing technology to design anti-counterfeiting patterns.

Benefits of technology

It realizes the preparation of high-resolution strong luminescent anti-counterfeiting materials, simplifies the preparation process, improves the flexibility of luminescent intensity and pattern design, solves the complex problems of luminescent intensity and pattern preparation of fluorescent anti-counterfeiting materials, and has versatility and high efficiency. Production capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193160A_ABST
    Figure CN119193160A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-counterfeiting material science, and relates to a high-resolution strong-luminescence anti-counterfeiting material and a preparation method thereof, the molecular formula of the anti-counterfeiting material is beta-NaYF4: Yb / Er / Gd, the molar ratio of Y: Yb: Er: Gd is 0.78: 0.2: 0.02: 0.03, and the anti-counterfeiting material can emit green light which is invisible to naked eyes and is located at 520-550 nm under the excitation of a 980 nm laser; the anti-counterfeiting material is hexagonal, uniform in size and excellent in morphology, emits strong green light, and can be used for preparing anti-counterfeiting ink; the anti-counterfeiting material is simple in preparation process, good in repeatability, easy to produce on a large scale and high in luminous intensity, an anti-counterfeiting pattern can be flexibly designed by combining the anti-counterfeiting material with an ink-jet printing technology, the problems that the luminous intensity of an existing fluorescent anti-counterfeiting material is poor and the preparation steps of the anti-counterfeiting pattern are complex are effectively solved, and the anti-counterfeiting material has certain universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the scientific and technical field of anti-counterfeiting materials, and relates to a high-resolution strong luminous anti-counterfeiting material and a preparation method thereof. Background Art

[0002] With the frequent occurrence of counterfeiting and copying of security documents, information security has become a hot topic, and how to scientifically and effectively prevent counterfeiting has become an urgent problem to be solved. Existing anti-counterfeiting technologies include physical anti-counterfeiting technology, chemical anti-counterfeiting technology, digital anti-counterfeiting technology, biological anti-counterfeiting technology, structural and packaging anti-counterfeiting technology, and texture anti-counterfeiting technology. Among them, chemical anti-counterfeiting technology is widely used, including thermosensitive anti-counterfeiting technology, chemical color change anti-counterfeiting technology, and fluorescent anti-counterfeiting technology. Thermosensitive anti-counterfeiting technology mainly uses thermosensitive anti-counterfeiting ink, also known as thermochromic ink or temperature-indicating ink. Its color change effect can be divided into reversible color change and irreversible color change to achieve anti-counterfeiting; chemical color change anti-counterfeiting technology is to use the principle that specific chemical substances change color under specific conditions for anti-counterfeiting. When encountering acid, alkali, oxidant and other chemical substances, the color of the anti-counterfeiting mark will change; fluorescent anti-counterfeiting technology is to develop new inks. Under ultraviolet light, the use of special fluorescent inks will show different colors of light, which is often used for anti-counterfeiting of bills, certificates, trademarks, etc.

[0003] The research on fluorescent inks has a long history. Commonly used fluorescent luminescent materials include up-conversion materials and down-conversion materials. The two materials have different luminescent properties and application fields. Down-conversion materials can convert short-wavelength light into longer-wavelength light. After the luminescent center in the down-conversion material absorbs high-energy photons, it emits the energy in the form of lower-energy photons through processes such as energy transfer and relaxation. UV-to-visible down-conversion materials and UV excitation sources are easy to obtain and easy to copy, so down-conversion luminescent inks are less used. Up-conversion materials can be excited by low-energy light and emit high-energy light. They are usually doped with lanthanides to convert near-infrared (NIR) excitation into visible emission and provide high photochemical stability, sharp emission bandwidth and large anti-Stokes shift. In addition, near-infrared excitation sources are difficult to obtain and will not excite standard down-conversion luminescent materials, which makes it possible to print patterns on highly fluorescent surfaces.

[0004] It is well known to those skilled in the art that the performance of anti-counterfeiting inks mainly comes from two aspects, namely, highly concealed luminescent materials and complex coding patterns. In the process of preparing up-conversion nanomaterials, the concentration of dopants and reactants, doping ions, fluorine sources, reaction time and temperature are all key parameters for accurately controlling the size and shape of up-conversion nanoparticles, affecting the luminescent properties of nanoparticles. When the type or ratio of doping elements is changed, up-conversion nanomaterials can emit light of different intensities under near-infrared excitation. Therefore, it is feasible to develop UCNPs to print high-luminescence intensity anti-counterfeiting patterns. For example, invention patent CN107641375A discloses an up-conversion luminescent ink based on lanthanide NaYF4, which can produce red, green and blue luminescent colors by changing the type of doped rare earth ions, has excellent characteristics, and the ink formula is difficult to copy, which improves the anti-counterfeiting performance of printed products. And how to improve the up-conversion emission intensity is an important challenge in producing highly concealed, high-resolution and high-luminescence anti-counterfeiting patterns.

[0005] In addition, there are some limitations in existing printing platforms. For example, screen printers can only print one ink in one printing process. Aerosol inkjet printers, although they have high spatial resolution, are time-consuming and complicated to operate due to their large and complex structures. Inkjet printing has been widely used in the manufacture of many complex structures. It has flexibility in selecting structural designs to produce complex security patterns, which can be quickly changed using a software-based printer control system, which can be applied to the printing of upconversion materials.

[0006] Based on the above problems, the present invention provides a high-resolution strong luminescent anti-counterfeiting material. When excited by a 980nm laser, the anti-counterfeiting material can emit green light at 520-550nm that is invisible to the naked eye; the anti-counterfeiting material is hexagonal in phase, uniform in size, excellent in morphology, and emits strong green light, and can be used to prepare anti-counterfeiting ink and is widely used in printing; the preparation process of the anti-counterfeiting material is simple, repeatable, easy to mass produce and has high luminescent intensity. When combined with inkjet printing technology, anti-counterfeiting patterns can be flexibly designed, effectively solving the current problem of luminescent intensity of fluorescent anti-counterfeiting materials and the problem of complicated preparation steps of anti-counterfeiting patterns, and has certain versatility. Summary of the invention

[0007] The primary purpose of the present invention is to provide a high-resolution strong luminescent anti-counterfeiting material. The molecular formula of the anti-counterfeiting material is β-NaYF4:Yb / Er / Gd. Under the excitation of a 980nm laser, the anti-counterfeiting material can emit green light at 520-550nm that is invisible to the naked eye.

[0008] Preferably, the molar ratio of Y:Yb:Er:Gd in the anti-counterfeiting material β-NaYF4:Yb / Er / Gd is 0.78:0.2:0.02:0.03.

[0009] Preferably, the diameter of the high-resolution strong luminescent anti-counterfeiting material is 30-40 nm.

[0010] Preferably, the anti-counterfeiting nanoparticles are hexagonal nanoparticles.

[0011] The second object of the present invention is to provide a method for preparing the high-resolution strong luminous anti-counterfeiting material, comprising the following steps:

[0012] (1) Dissolve the Er-containing 3+ , Gd 3+ , Y 3+ and Yb 3+ The compound solution was added to the mixed solution containing oleic acid and octadecene, the solution was stirred at room temperature, slowly heated to 110°C, kept for 1 hour, and then heated to 160°C under a nitrogen atmosphere and heated for another 1 hour;

[0013] (2) The solution obtained in step (1) was cooled to 50° C., a methanol solution of NH4F and NaOH was added, and the mixture was stirred at 50° C. for 1 h. The temperature was raised to 70° C. to evaporate the methanol;

[0014] (3) The mixture obtained in step (2) is heated to 110° C. and stored under a nitrogen atmosphere for 1 h to remove residual oxygen and water, then heated to 290-310° C. and stored for 1 h to 1.5 h. The product is precipitated with ethanol, collected by centrifugation at 10,000 rpm for 10 min, washed with ethanol and cyclohexane, and dispersed in cyclohexane for later use.

[0015] Preferably, the Er-containing 3+ , Gd 3+ , Y 3+ and Yb 3+ The compounds are all hydrated chlorides.

[0016] The third object of the present invention is to provide the use of the high-resolution strong luminous anti-counterfeiting material in the preparation of anti-counterfeiting ink.

[0017] The fourth object of the present invention is to provide the use of the high-resolution strong luminescent anti-counterfeiting material in the preparation of a preparation for fluorescent in vivo imaging.

[0018] The fifth object of the present invention is to provide an anti-counterfeiting ink, wherein the anti-counterfeiting ink comprises the anti-counterfeiting material β-NaYF4:Yb / Er / Gd.

[0019] Preferably, the anti-counterfeiting ink is prepared by preparing the anti-counterfeiting material β-NaYF4:Yb / Er / Gd into a cyclohexane solution and mixing it with glycerol in a ratio of 9:1.

[0020] The present invention has the following beneficial effects: the present invention provides a high-resolution strong luminescent anti-counterfeiting material, the molecular formula of the anti-counterfeiting material is β-NaYF4:Yb / Er / Gd, and the anti-counterfeiting material can emit green light at 520-550nm that is invisible to the naked eye under the excitation of a 980nm laser; the anti-counterfeiting material is in a hexagonal phase, has uniform size, excellent morphology, and emits strong green light, can be used to prepare anti-counterfeiting ink, and is widely used in printing; the anti-counterfeiting material has a simple preparation process, good repeatability, is easy to mass produce, and has high luminescent intensity. When combined with inkjet printing technology, anti-counterfeiting patterns can be flexibly designed, effectively solving the problem of the luminescent intensity of current fluorescent anti-counterfeiting materials and the problem of complicated steps in preparing anti-counterfeiting patterns, and has certain versatility. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Fluorescence spectra of β-NaYF4:Yb / Er upconversion materials prepared by doping with different Yb amounts;

[0022] Figure 2 Scanning transmission electron microscopy (STEM) images of β-NaYF4:Yb / Er and β-NaYF4:Yb / Er / Gd;

[0023] Figure 3 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of β-NaYF4:Yb / Er (a) and the corresponding energy dispersive X-ray spectroscopy (EDX) images (bf).

[0024] Figure 4 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of β-NaYF4:Yb / Er / Gd (a) and the corresponding energy dispersive X-ray spectroscopy (EDX) imaging (bg);

[0025] Figure 5 X-ray diffraction patterns (XRD) of β-NaYF4:Yb / Er and β-NaYF4:Yb / Er / Gd;

[0026] Figure 6 Fluorescence spectrum of β-NaYF4:Yb / Er / Gd green light upconversion material. The inset is the luminescence image of the green light upconversion material under 980nm laser irradiation.

[0027] Figure 7 Fluorescence comparison of β-NaYF4:Yb / Er and β-NaYF4:Yb / Er / Gd;

[0028] Figure 8 Fluorescence photograph of the high-resolution strong luminescent anti-counterfeiting material prepared in Example 3-6 under 980nm laser excitation;

[0029] Fig. 9 Anti-counterfeiting pattern after being excited by 980nm laser. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. The following examples are only used to illustrate the technical solution of the present invention but are not intended to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should all be included in the scope of the claims of the present invention.

[0031] It should be noted that, in the following examples, unless otherwise specified, the methods used are all conventional methods.

[0032] In the following examples, unless otherwise specified, the reagents and consumables used can be purchased from the market.

[0033] Example 1. Synthesis of β-NaYF4:Yb / Er (0.4 / 0.04 mol) Nanoparticles

[0034] Dissolve 2 mmol of Er in 2 mL of water. 3+ , Y 3+ and Yb 3+ The compound solution was added to a mixed solution containing 14 mL of oleic acid and 30 mL of octadecene (the amounts of Yb and Er were 1.2 / 0.04 mol, 0.4 / 0.04 mol, and 0.04 / 0.04 mol, respectively). The solution was stirred at room temperature for 20 min, then slowly heated to 110 ° C, kept for 1 h, and then heated to 160 ° C under a nitrogen atmosphere and heated for another 1 h. After cooling to 50 ° C, 20 mL of a methanol solution of NH4F (296.32 mg, 8 mmol) and NaOH (200 mg, 5 mmol) was added and stirred at 50 ° C for 1 h. Subsequently, the temperature was increased to 70 ° C to remove methanol. After methanol was evaporated, the mixture was heated to 110 ° C and kept for 1 h under a nitrogen atmosphere to remove residual oxygen and water. Then it was heated to 300 ° C and kept for 1 h. The product was precipitated with ethanol, collected by centrifugation at 10000 rpm for 10 min, washed several times with ethanol and cyclohexane, and finally dispersed in cyclohexane for use.

[0035] Figure 1 The fluorescence spectra of upconversion materials prepared by doping with different Yb contents are shown in the figure. From the figure, we can see that the fluorescence intensity of β-NaYF4:Yb / Er (0.4 / 0.04mol) is the strongest. Therefore, we choose it as the optimal condition for subsequent Gd doping.

[0036] Example 2: Synthesis of β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06 mol) Nanoparticles

[0037] The preparation method of the above-mentioned high-resolution strong luminous anti-counterfeiting material comprises the following steps:

[0038] Dissolve 2.06 mmol of Er in 2 mL of water. 3+ , Gd 3+ , Y 3+ and Yb 3+ The compound solution was added to a mixed solution containing 14 mL of oleic acid and 30 mL of octadecene. The solution was stirred at room temperature for 20 min, then slowly heated to 110 ° C, kept for 1 h, and then heated to 160 ° C under a nitrogen atmosphere and heated for another 1 h. Cooled to 50 ° C, 20 mL of a methanol solution of NH4F (296.32 mg, 8 mmol) and NaOH (200 mg, 5 mmol) was added, and stirred at 50 ° C for 1 h. Subsequently, the temperature was increased to 70 ° C to remove methanol. After the methanol evaporated, the mixture was heated to 110 ° C and kept for 1 h under a nitrogen atmosphere to remove residual oxygen and water. Then heated to 300 ° C and kept for 1 h. The product was precipitated with ethanol, collected by centrifugation at 10000 rpm for 10 min, washed several times with ethanol and cyclohexane, and finally dispersed in cyclohexane for use.

[0039] Scanning transmission electron microscopy (STEM) images show that compared with β-NaYF4:Yb / Er (0.4 / 0.04mol) nanocrystals ( Figure 2 a, b), the synthesized β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) nanocrystals ( Figure 2 c, d) Smaller and more uniform particle size. Dopants with different ionic radii can change the lattice of lanthanide-doped particles, thereby changing the crystal field and coordination environment of lanthanides. This versatility may lead to changes in the size and morphology of the synthesized UCNPs. β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) is ellipsoidal in shape with uniform particle size and good dispersion. The change in the surface electron charge density of small-sized nanocrystals greatly slows down the diffusion of negatively charged F- ions to the surface due to the increase in charge repulsion, resulting in a reduction in the size of NaYF4 nanocrystals. The average size of β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) nanocrystals is 30nm.

[0040] Figure 3High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) images and corresponding energy-dispersive X-ray spectroscopy (EDX) imaging of β-NaYF4:Yb / Er (0.4 / 0.04 mol) show that Er, F, Na, Yb, and Y are uniformly distributed.

[0041] Figure 4 The HAADF-STEM image and the corresponding energy dispersive x-ray spectroscopy (EDX) mapping image of β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06 mol) are shown, indicating the presence of Er, F, Na, Yb, Y and Gd.

[0042] Figure 5 The X-ray diffraction pattern (XRD) of β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) in the experiment showed that all the diffraction peaks were attributed to the hexagonal phase structure of NaYF4 (JCPDS no.16-0334). It is reported that hexagonal (β-NaYF4:Yb, Er) nanoparticles have higher upconversion efficiency than cubic (α-NaYF4:Yb, Er) nanoparticles.

[0043] Gd-doped 3+ The XRD spectra before and after show that Gd-doped 3+ The peak shifts to lower diffraction angles, indicating that the larger Gd 3+ Ions replace Y 3+ ions, resulting in an expansion of the unit cell volume. Importantly, we also observed that Gd 3+ The diffraction peak becomes broader, indicating that the average grain size decreases, which is consistent with the STEM image.

[0044] Figure 6 This is the fluorescence spectrum of β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) green light upconversion material. It can be seen that the light emitted with 548nm as the emission center is very strong. Under 980nm laser irradiation, the naked eye can see that the β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) solution exhibits very strong green light emission.

[0045] Figure 7 This is a fluorescence comparison diagram of β-NaYF4:Yb / Er (0.4 / 0.04mol) and β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol). From the figure, we can see that the green-red intensity ratio of fluorescence is higher after doping with Gd, so we obtained the material β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06mol) with high green light intensity.

[0046] Example 3-6: Preparation of a high-resolution, strong-luminescent anti-counterfeiting material

[0047] Dissolve 2.06 mmol of Er in 2 mL of water. 3+ , Gd 3+ , Y 3+ and Yb 3+ The compound solution was added to a mixed solution containing 14 mL of oleic acid and 30 mL of octadecene. The solution was stirred at room temperature for 20 min, then slowly heated to 110 ° C, kept for 1 h, and then heated to 160 ° C under a nitrogen atmosphere and heated for another 1 h. Cooled to 50 ° C, 20 mL of a methanol solution of NH4F (296.32 mg, 8 mmol) and NaOH (200 mg, 5 mmol) was added, and stirred at 50 ° C for 1 h. Subsequently, the temperature was increased to 70 ° C to remove methanol. After the methanol evaporated, the mixture was heated to 110 ° C and kept for 1 h under a nitrogen atmosphere to remove residual oxygen and water. Then heated to the above temperature and kept for a certain period of time. The product was precipitated with ethanol, collected by centrifugation at 10000 rpm for 10 min, washed several times with ethanol and cyclohexane, and finally dispersed in cyclohexane for use.

[0048] Grouping Heating temperature(℃) Storage time (h) Example 3 300 1.5 Example 4 290 1 Example 5 310 1 Example 6 310 1.5

[0049] Characterize the fluorescence images of the high-resolution strong luminescent anti-counterfeiting materials prepared in Examples 3-6 under 980nm laser excitation, such as Figure 8 As shown, it can be found that under the above reaction temperature, reaction time and ratio, high-resolution strong luminescent anti-counterfeiting materials with good performance can be prepared.

[0050] Embodiment 7,

[0051] The application of the above-mentioned high-resolution strong luminescent anti-counterfeiting material has the following steps: mixing β-NaYF4:Yb / Er / Gd (0.4 / 0.04 / 0.06 mol) cyclohexane solution with glycerol in a ratio of 9:1 to make an ink, using software to design the anti-counterfeiting pattern, and using inkjet printing to draw the anti-counterfeiting pattern.

[0052] Fig. 9 This is the luminescence image of the anti-counterfeiting pattern under 980nm laser excitation.

[0053] The invention provides a high-resolution strong luminous anti-counterfeiting material, the molecular formula of the anti-counterfeiting material is β-NaYF4:Yb / Er / Gd, and the anti-counterfeiting material can emit green light at 520-550nm which is invisible to the naked eye under the excitation of a 980nm laser; the anti-counterfeiting material is in a hexagonal phase, has uniform size, excellent morphology, and emits strong green light, can be used to prepare anti-counterfeiting ink, and is widely used in printing; the anti-counterfeiting material has a simple preparation process, good repeatability, is easy to mass produce, and has high luminous intensity, and can be combined with inkjet printing technology to flexibly design anti-counterfeiting patterns, effectively solving the problem of the luminous intensity of current fluorescent anti-counterfeiting materials and the problem of complicated steps for preparing anti-counterfeiting patterns, and has certain versatility.

[0054] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0055] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0056] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A high-resolution, strong-luminescent anti-counterfeiting material, characterized in that: The molecular formula of the anti-counterfeiting material is β-NaYF4:Yb / Er / Gd. Under the excitation of a 980nm laser, the anti-counterfeiting material can emit green light at 520-550nm which is invisible to the naked eye.

2. The high-resolution, strong-luminescent anti-counterfeiting material according to claim 1, characterized in that: The molar ratio of Y:Yb:Er:Gd in the anti-counterfeiting material β-NaYF4:Yb / Er / Gd is 0.78:0.2:0.02:0.

03.

3. The high-resolution, strong-luminescent anti-counterfeiting material according to claim 1, characterized in that: The diameter of the high-resolution strong luminescent anti-counterfeiting material is 30-40nm.

4. The high-resolution, strong-luminescent anti-counterfeiting material according to claim 1, characterized in that: The anti-counterfeiting nanoparticles are hexagonal nanoparticles.

5. The method for preparing the high-resolution strong luminous anti-counterfeiting material according to claim 1, characterized in that: The steps include: (1) Dissolve the Er-containing 3+ , Gd 3+ , Y 3+ and Yb 3+ The compound solution was added to the mixed solution containing oleic acid and octadecene, the solution was stirred at room temperature, slowly heated to 110°C, kept for 1 hour, and then heated to 160°C under nitrogen atmosphere and heated for another 1 hour; (2) The solution obtained in step (1) was cooled to 50° C., a methanol solution of NH4F and NaOH was added, and the mixture was stirred at 50° C. for 1 h. The temperature was raised to 70° C. to evaporate the methanol; (3) The mixture obtained in step (2) is heated to 110° C. and stored under a nitrogen atmosphere for 1 h to remove residual oxygen and water, then heated to 290-310° C. and stored for 1 h to 1.5 h. The product is precipitated with ethanol, collected by centrifugation at 10,000 rpm for 10 min, washed with ethanol and cyclohexane, and dispersed in cyclohexane for later use.

6. The method for preparing the high-resolution strong luminous anti-counterfeiting material according to claim 5, characterized in that: Step (1) containing Er 3+ , Gd 3+ , Y 3+ and Yb 3+ The compounds are all hydrated chlorides.

7. Use of the high-resolution, strong-luminescent anti-counterfeiting material according to any one of claims 1 to 4 in the preparation of anti-counterfeiting ink.

8. Use of the high-resolution, strong-luminescent anti-counterfeiting material according to any one of claims 1 to 4 in the preparation of a preparation for fluorescent in vivo imaging. 9.An anti-counterfeiting ink, characterized in that: The anti-counterfeiting ink comprises the anti-counterfeiting material β-NaYF4:Yb / Er / Gd.

10. The anti-counterfeiting ink according to claim 9, characterized in that: The anti-counterfeiting ink is prepared by preparing the anti-counterfeiting material β-NaYF4:Yb / Er / Gd into a cyclohexane solution and mixing it with glycerol in a ratio of 9:1.

Citation Information

Patent Citations

  • Composite nanostructure based on rare earth up-conversion luminescent material as well as preparation method and application of composite nanostructure

    CN104449731A